Analysis Of Smallholder Decision-Making In Replanting Programs - Tiara Pertiwi; Abdul Rahman Sidik; M Rexy Dimas Nasrullah; Mulono Apriyanto; Marlina Marlina (Akademi Komunitas Perkebunan Yogyakarta, 2023)
This study is to investigate the amount of decision-making participation by smallholders in the palm oil replanting programme as well as the factors that impact the participation of smallholders in this programme. This study was carried out by performing survey research with quantitative methodologies, which included observation, interviews, the use of questionnaires, and documenting of previous findings. The evaluation was carried out in the Kempas District of the Indragiri Hilir Regency between the months of September and December of 2022. In this study, the number of samples was decided to be 38 persons using the technique of Simple Random Sampling from farmers who engaged in the oil palm replanting programme. Data was collected using questionnaires that had previously been evaluated for their validity and reliability. The Likert scale will be used in the data analysis approach to measure the level of smallholder decision making in oil palm replanting initiatives, and multiple linear regression analysis will be utilised in the data processing.According to the findings of the research project, the interpretation of the degree of smallholder decision-making in the oil palm replanting programme was placed in the questionable category 53.4% of the time. After doing a regression analysis. When it comes to smallholder decision-making in oil palm replanting projects, the factors of age, education, farm area, experience, income, social environment, economic environment, and extension activities all play a key role simultaneously. Farming area and years of experience are two of the factors that play a key role in the decisions made by smallholder farmers in the oil palm replanting programme carried out in the Kempas District of the Indragiri Hilir Regency of the Riau Province